Effect of Alkaline treatment on the characteristics of pineapple leaves fibre and PALF/PP biocomposite - S. Gnanasekaran; N.I.A.A. Nordin; M.M.M Hamidi; J.H. Shariffuddin (Journal of Mechanical Engineering and Sciences, 2021)
Pineapple leaves fibre (PALF) is one of the natural fibre that hashigh potential to substitute non-renewable synthetic fibre in thermoplastic products.The PALF were alkali treated withdifferent concentrationsof NaOH. Untreated and alkali treated PALF were characterizedusing Thermal Gravimetric Analysis (TGA)and Scanning Electron Microscopy (SEM)to determine the thermal stability and surface morphology of the fibres respectively. Biocomposites were prepared by reinforced alkali treated and untreated PALF withpolypropylene (PP) matrix. Tensile properties and water absorption analysis of PALF/PP biocomposites were studied.Biocomposite with 8 wt.% of alkali treated PALFexpress excellentthermal stability, with maximum degradation temperature at 270 °Cwhich is a 7.17% improvement compared to untreated PALF. This biocomposite alsohad increasedtensile strength(116 MPa)with 43%improvement compared to untreated PALF/PP(66 MPa)biocompositeand had lower water absorption at 6% compared to untreated biocomposite which at21%. Hence, alkali treated PALF is able to improve the characteristic of PALF and increase the compatibility between fibreand polymerby reducing hemicellulose and lignin components.